2017
DOI: 10.1111/grs.12174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UV radiation on the process of wilting and application of additives at ensiling on the fermentation quality of Siberian wildrye silage on the Qinghai‐Tibetan plateau

Abstract: Effects of lactic acid bacteria (LAB) and formic acid (FA) on silage quality of ultraviolet (UV)-radiated Siberian wildrye (Elymus sibiricus L.) were studied on the Qinghai-Tibetan plateau. Siberian wildrye seeds were sown in early April, 2012 and harvested in 2013, 2014 and 2016. Fresh forage was radiated for 0, 4 and 8 h under ambient/laboratory UV radiation conditions during the wilting process, and then mixed with LAB inoculant (10 5 cfu g À1 fresh matter [FM]) and FA (3 mL kg À1 FM), respectively, no addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The fermentation of the wilted silage exhibited a higher target ensiling DM due to elevated total VFA and LA concentrations. The ensiling quality at wilted is usually better than that fresh [ 21 ], which is consistent with the results of this study. The presence of BA in silage is undesirable given that its generation is an energy-waste metabolism and BA>5 g/kg DM is an indicator of substantial clostridial activity reducing feed intake and causing health issues [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…The fermentation of the wilted silage exhibited a higher target ensiling DM due to elevated total VFA and LA concentrations. The ensiling quality at wilted is usually better than that fresh [ 21 ], which is consistent with the results of this study. The presence of BA in silage is undesirable given that its generation is an energy-waste metabolism and BA>5 g/kg DM is an indicator of substantial clostridial activity reducing feed intake and causing health issues [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…The pH of filtrate was determined by pH meter (PHSJ‐4F; Shanghai INESA Scientific Instrument Co., Ltd). Filtrate of about 10 ml was subjected to centrifugation (4,500 × g , 15 min, 4°C), and the supernatant was analyzed for lactic acid, acetic acid, propionic acid, and butyric acid using high‐performance liquid chromatography (Li, Tang, et al, 2017). Ammonia‐N was determined by the method of Broderick and Kang (1980).…”
Section: Methodsmentioning
confidence: 99%
“…For example, many phyllosphere bacteria are pigmented and use these pigments to protect against high levels of UV radiation on leaf surfaces ( 13 , 14 ). Similarly, Li et al ( 15 ) reported that 8 h of UV exposure significantly decreased the LAB counts on Siberian wildrye. The yeast count also decreased during the day, suggesting their high sensitivity to the dynamic diurnal environment.…”
Section: Discussionmentioning
confidence: 81%